Determination of critical micelle concentration (CMC) of corrosion inhibitor via electrochemical measurement - Jaal, R.A. (Asian Research Publishing Network, 2016)
The critical micelle concentration (CMC) of an imidazoline-based corrosion inhibitor in CO2-saturated 3 NaCl solution was determined via electrochemical measurements, namely electrochemical impedance spectroscopy and linear polarization resistance. The electrochemical parameters, polarization resistance (Rp) and charge transfer resistance (Rct), were plotted against the inhibitor concentrations. CMC of the studied inhibitor was determined from the plots, where the slope changed their values. Analysis of the impedance data revealed that the adsorbed inhibitor films had different structures, which were influenced by the concentration of the inhibitor. Â© 2006-2016 Asian Research Publishing Network (ARPN).